Decision-Making in Crisis Situations - Sauvagnargues, Sophie (Wiley-ISTE, 2018)
This book presents concepts and methods for optimal training for decision making in crisis situations. After presenting some general concepts of decision-making during crisis situations, it presents various innovations for optimal training, such as serious games, scenario design, adapted animation of crisis exercises, observation and debriefing of exercises related to pedagogical objectives.